Affordances for sharing domain-specific and complex knowledge on enterprise social media. (December 2018) - Pee, L.G.
Highlights: The affordance of visibility eases the sharing of domain-specific knowledge. The affordances of association and editability ease the sharing of complex knowledge. There are significant interactions between affordances and knowledge attributes. Enterprise social media could facilitate the sharing of domain-specific and complex knowledge. Abstract: Many organizations have implemented enterprise social media (ESM) to better connect employees and promote knowledge sharing. Prior studies indicate that employees often use ESM to access knowledge in other domains or complex knowledge. But connecting employees is only part of the picture – while ESM offer the possibility of accessing domain specific and complex knowledge, the flow of such knowledge might remain inhibited by the perceived effort required to codify them for sharing. This study identifies salient ESM affordances that can alleviate the perceived effort of sharing domain-specific and complex knowledge. Results of a survey of 303 employees working in organizations using ESM indicate that domain-specific knowledge is perceived as less effortful to codify when the affordance of visibility is strong (i.e., the affordance negatively moderates the positive relationship between knowledge specificity and perceived codification effort), and complex knowledge is perceived as less effortful to codify when the affordances of association and editability are strong. These findings indicate that it is necessary to consider both knowledge attributes and ESM affordances and their interactions when understanding knowledge sharing using ESM.